The principles of the Cuius regio project and the history of Silesia between 1526 and 1740 - Wąs, Gabriela (Publishing House eBooki.com.pl, 2014)
The articles gathered in the volume present the second stage of research on the region of Silesia, encompassing the period 1526-1740 and conducted under the patronage of the European Science Foundation as a portion of the project “Cuius regio. An analysis of the cohesive and disruptive forces determining the attachment and commitment of (groups of) persons to and cohesion within regions”. The objective of the project is to identify the factors occurring in each period which consolidated the Silesia region, or alternatively led to its disintegration, in several primary areas: administrative, economic and cultural/artistic. The specificity of the region’s history during its time under Habsburg rule led to a focus of attention on the political and cultural orientations of the people and social groups of Silesia. Their activities and attitudes were treated as the primary indicators revealing the social dimension of efforts to unify the region of Silesia with other countries of the Kingdom of Bohemia, as well as with the other political and territorial organisms composing the Habsburg dominion in Central Europe. These processes were also observed from the perspective of the political objectives pursued by Czech monarchs in that period. Analyses of events and phenomena of the time revealed periods of royal anti-regional policies towards Silesia accompanied by periods of policies intended to strengthen its regional identity within the Kingdom of Bohemia, within the context of efforts to achieve the overarching goal consisting in the monarchical centralization of authority.
Keywords: Silesia; regional history; regionalism